2019
DOI: 10.3390/molecules24173173
|View full text |Cite
|
Sign up to set email alerts
|

New Artificial Biomimetic Enzyme Analogues Based on Iron(II/III) Schiff Base Complexes: An Effect of (Benz)imidazole Organic Moieties on Phenoxazinone Synthase and DNA Recognition ‡

Abstract: Elucidation of the structure and function of biomolecules provides us knowledge that can be transferred into the generation of new materials and eventually applications in e.g., catalysis or bioassays. The main problems, however, concern the complexity of the natural systems and their limited availability, which necessitates utilization of simple biomimetic analogues that are, to a certain degree, similar in terms of structure and thus behaviour. We have, therefore, devised a small library of six tridentate N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…For instance, Aleksandra Bocian et al prepared several iron complexes comprising 2-aminobenzimidazole ligands and evaluated their potential as artificial biomimetic enzyme analogues. [6] 2-Aminobenzimida-zole was also utilized as a ligand to modify the structures of zeolitic imidazolate frameworks (ZIFs), thereby adjusting the properties of the corresponding materials. [7] Besides, the 2-aminobenzimidazole skeleton is prevailing in chemical sensors for the detection of anions [8] as well as in corrosion inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Aleksandra Bocian et al prepared several iron complexes comprising 2-aminobenzimidazole ligands and evaluated their potential as artificial biomimetic enzyme analogues. [6] 2-Aminobenzimida-zole was also utilized as a ligand to modify the structures of zeolitic imidazolate frameworks (ZIFs), thereby adjusting the properties of the corresponding materials. [7] Besides, the 2-aminobenzimidazole skeleton is prevailing in chemical sensors for the detection of anions [8] as well as in corrosion inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Other than the enzyme-catalyzed transformation, several methods have been developed for synthesizing phenazine and phenoxazinone from substituted aromatic amines, but most of them use organic solvents and metal catalyst and their reaction conditions are harsh, with a low product yield, slow reaction rate, and limited substrate scope (Scheme ). Therefore, a reasonable yield of substituted phenazine and phenoxazinone scaffolds via a metal-free catalyst is desirable. Nowadays, visible-light photoredox catalysis has received immense attention among organic chemists; unlike the traditional thermal process, it occurs under mild conditions and offers a clean, synthetic technology that meets green chemistry principles .…”
mentioning
confidence: 99%
“…In contrast, [Fe(Lx) 2 ](OTf) 2 complexes exhibited bulky cations which resulted in the interaction with the negatively charged backbone of DNA. This showed that the benzimidazole moiety adequately blocks the excess species from intercalation or some other critical interaction with nucleic acids and the imidazole substituent can be utilized for tuning of the interaction strength [147] …”
Section: Resultsmentioning
confidence: 99%
“…This showed that the benzimidazole moiety adequately blocks the excess species from intercalation or some other critical interaction with nucleic acids and the imidazole substituent can be utilized for tuning of the interaction strength. [147] Schiff base-linked imidazole-modified polylysine with a reversible-PEGylation catiomer (90) of high-efficiency gene engineered by Cai et al (2015) is shown in Figure 38. The reversible PEGylation was presented for in-vivo dissemination, just as particular PEG separation to expand the cell internalization, while presenting Schiff-base connected imidazole buildups into polylysine was relied upon to speed up the endosomal escape of the DNA payload, just as work with intracellular DNA unloading and delivery, in this manner fundamentally improving gene delivery effectiveness.…”
Section: Chemistryselectmentioning
confidence: 99%